Pyknotic Nuclei and Change in N/C Ratio of Heptocytes by Consumption of Allicin Present in Garlic Extract - Asma Siddique, Muhammad Sohail Aslam, Saba Amjad, Asma Zulfiqar, Saqib Mansoor, Sibgha Fatima, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Garlic (allium sativum) is given as herbal medicine due to its antimalignanat effect. It has been reported that allium vegetables have marked anticancer effect against stomach and colorectal carcinomas. Organosulfur compounds in garlic activate the metabolizing enzymes and cytochrome P450s to detoxify carcinogens and other foreign compounds like lead. These components act as anticarcinogenic for gastrointestinal tract, lungs and mammary gland in experimental animals. Aim: To evaluate the dose range of garlic (allium sativum) to induce the antitumor effect. Study design: Experimental study Place and duration of study: Department of Anatomy, Shaikh Zayed Postgraduate Medical Institute, Lahore from 1st October 2013 to 31st March 2014. Methodology: Forty five Wistar albino rats of both sexes weighing between 250-350 grams were selected randomly. Two different doses of 500 and 1000 mg/kg of fresh garlic extract were given to the animals by orogastric tube for thirty days. After this period the analysis of quantitative parameters including the diameter of the hepatocytes and hapatic nucleus were recorded and nucleus to cell ratios (N/C Ratios) were calculated. Results: The atrophic changes on the size of hepatocytes and their nucleus is noted in both experimental group B and C as compared to control group A (P<0.001). Conclusion: There is a significant atrophic change, appearance of pyknotic nuclei indicating the apoptosis. That is leading to decrease in N/C ratio, beneficial in producing the anticarcinigen effect. Keywords: Garlic (allium sativum), hepatocytes, atrophy, pyknotic nuclei, albino rats